Non-invasive beat to beat arterial blood pressure during non-REM sleep in obstructive sleep apnoea and snoring. - Davies, R; Crosby, J; Vardi-Visy, K; Clarke, M; Stradling, JR (1994)
BACKGROUND: Obstructive sleep apnoea, and possibly snoring, are associated with a poorly understood increase in cardiovascular mortality which may be explained by their effects on systemic blood pressure during sleep. This study compares changes in mean blood pressure during obstructive sleep apnoea and snoring without apnoeas with those in matched control subjects during non-REM sleep. METHODS: Eighteen men with obstructive sleep apnoea, 16 men who snored without apnoeas, and 34 control subjects matched for age, sex, obesity, smoking, and alcohol intake were studied. During polysomnography non-invasive mean blood pressure (Finapres) was recorded from each cardiac cycle during non-REM sleep and averaged over a 10 minute period. This was compared with the blood pressure during 10 minutes before sleep onset. The changes in the patients' sleeping blood pressure were compared with those in their individually matched control subjects. RESULTS: Compared with the control subjects the change in mean (SD) arterial blood pressure between being awake and asleep was higher during obstructive sleep apnoea (+6.5 (9) mm Hg v-2 (6.5), difference 8.5 (11)), and the rise from wakefulness to sleep in the obstructive sleep apnoea group was itself significant. The average mean arterial pressure was not raised in those who snored without apnoeas compared with either the control subjects or during wakefulness. CONCLUSIONS: Average mean arterial pressure is higher during obstructive sleep apnoea than it is during wakefulness, while normal subjects show a fall in blood pressure at sleep onset. This sleep related rise in blood pressure may contribute to the excess cardiovascular morbidity and mortality experienced by patients with this condition.